Unveiling Creativity Elements in YouTube Narrative Videos for Ninth-Grade Junior High School Students - Nugraha, Nalika Ligar Katiasa; Permana, Sudarya; Agustina, Imas Wahyu (STAIRS: English Language Education Journal, 2023)
Creative narrative videos posted on YouTube have been proven to help students learn the narrative text and enhance students’ creativity toward making an excellent creative product. Along with the advantages, there are challenges and risks that teachers must consider since YouTube is an open-access video-sharing platform. This study aims to see whether narrative videos posted on YouTube meet creativity elements that can help ninth-grade junior high school students learn narrative text. This study used a qualitative method with content analysis to analyze fifteen narrative videos from three YouTube channels; Dongeng Kita, English Fairy Tales, and Gigglebox. The selected fifteen videos have been uploaded within the last seven years and are addressed to teenage viewers. Using the framework from D'Souza (2021), the findings show that the selected narrative videos fulfilled around 30% to 80% of the creativity elements. The audience immersive experience aspect, with a percentage of 45%, is the most dominant aspect of the narrative video's creativity elements. In contrast, the development and control aspect is the least in the creativity elements of narrative video, with a percentage of 25,5%. The narrative videos demonstrate diversity, a distinction or feature that distinguishes a narrative video from the previous version (narrative text). This study is expected to be a recommendation for teachers in choosing narrative videos on YouTube to support their teaching materials and simultaneously enhance students' creative thinking skills.